Never too old to work: managing an age diverse workforce. Issue 3 (15th April 2020) - Butler, Steve
Abstract : Purpose: Setting the scene of a workforce that is living and working longer. Changing demographics are going to have a huge impact on the workplace and businesses need to get ahead of the curve. Design/methodology/approach: Age stereotyping is one of the biggest issues faced by companies today. Companies need to focus on recruiting and retaining people based on their ability and capabilities, not their age. Findings: In an intergenerational team, the team members are not artificially defined or divided by age; it is their talent that is important. Employers must recognize the unique skills and experiences each team member brings. Originality/value: The expectation of flexibility among younger employees is now ingrained. If businesses want to recruit and retain younger workers, they must embrace this way of working. Flexibility is just as important for older workers, especially those with caring responsibilities (children or elderly parents.) Employers need to adapt their benefits package to appeal to all.